EFFICIENCY OF RECOMBINANT TNF-BINDING PROTEIN FROM VARIOLA VIRUS IN A MODEL OF COLLAGEN-INDUCED ARTHRITIS - D. D. Tsyrendorzhiev; S. V. Sennikov; I. A. Orlovskaya; I. P. Gileva; I. A. Ryazankin; L. B. Toporkova; V. V. Kurilin; Yu. A. Lopatnikova; A. A. Grydina; S. N. Schelkunov (Медицинская иммунология, 2014)
Abstract. This paper presents the results of the research on the effectiveness of recombinant TNF-binding protein of variola virus (VARV-CrmB) in a model of collagen-induced arthritis (CIA) in mice (CBAxC57Bl6) F1. The introduction of VARV-CrmB and polyclonal antibody to recombinant mouse TNF (poly-AbMuTNF) led to an improvement of clinical manifestations of CIA by reducing the swelling and increasing the mobility of mice limbs. The introduction of VARV-CrmB and poly-AbMuTNF reduced the number of neutrophilic granulocytes and granulocytic precursors. The introduction of VARV-CrmB and poly-AbMuTNF into mice decreased collagenolysis in the blood serum and the content of glycosaminoglycans at the early stages of experimentation. Treatment with VARV-CrmB and poly-AbMuTNF of mice with CIA significantly decreased the chemiluminescence response of blood leukocytes. VARV-CrmB exerted more pronounced inhibitory effect on the production of reactive oxygen metabolites by blood leukocytes of mice with CIA than poly-AbMuTNF. Improvement of clinical condition of the mice with CIA has a more prolonged effect following introduction of the VARV-CrmB than after injection of poly-AbMuTNF. The results suggest the recombinant viral protein VARVCrmB to be a new potential TNF-antagonist.